The "Jewel of Muscat" Project: reconstructing an early ninth-century CE shipwreck - Vosmer, Tom; Belfioretti, Lụca; Staples , Eric; Ghidoni, Alessandro (Proceedings of the Seminar for Arabian Studies, 2011)
The Jewel of Muscat Project focused on the reconstruction, based on an early ninth-century shipwreck, of a sewn-plank ship excavated in 1998-1999 off Belitung Island, Indonesia. Analysis of the surviving structure indicated that the ship was originally from the western Indian Ocean, and probably the Arabian Peninsula. The project comprehensively documented the research and construction of this vessel in Oman, and the sailing to Singapore. This paper addresses the technical aspects involved with building the 18 m vessel from the inevitably incomplete excavated remains, and compares the archaeological evidence with the modern reconstruction. It examines the methodological issues involved with creating a conceptual bridge between the fields of archaeology and ethnographic boatbuilding. The paper also provides an overview of the navigation and sailing performance of the vessel, documented by modern instruments. The project deepened our understanding of Early Islamic maritime technology and seafaring, while simultaneously documenting the ancient shipbuilding and navigation traditions of the Arabian Peninsula, which are rapidly becoming extinct.